Genome‐wide association study for desirable traits in the Pacific oyster Crassostrea gigas (Thunberg). (7th June 2022) - Liu, Sheng; Li, Li; Shi, Ruihui; Wang, Wei; Wu, Fucun; Zhang, Guofan
Abstract: The Pacific oyster, Crassostrea gigas (Thunberg), from the northwest Pacific Ocean has been introduced for aquaculture in many areas. Despite its economic importance, genetic dissection for growth, shell shape and yield traits have not been reported thoroughly. To explore single nucleotide polymorphisms (SNPs) associated with desired traits in Pacific oyster, a genome‐wide association study (GWAS) was conducted based on the 190 K high‐density SNP array. Growth, shell shape and yield traits, including shell height, condition index and dressing percentage, were studied. Moderate to high phenotypic correlations between shell height and other growth‐related traits in the studied wild population were observed ( r = 0.38–0.77, p < 0.05), and the dressing percentage was correlated with the condition index ( r = 0.6, p < 0.05). The condition index had a moderate positive correlation with glycogen and fat content ( r = 0.22–0.35, p < 0.05). The results of GWAS indicated that 11 SNPs were significantly associated with the studied traits. Shell height, body weight and soft body weight were all associated with a significant nonsynonymous SNP (scaffold731_92759), phenotypic variation explanations associated with this single SNP are 8.59%, 8.12% and 8.13%, respectively. This SNP is located in the protein‐coding region of the serine protease inhibitor dipetalogastin, which is thought to be involved in food digestion and absorption. This polymorphism may affect the ability of dipetalogastin to inhibit serine proteases, thereby affecting the oyster's growth. This study identified new candidate genes and SNPs related to oyster growth, which is useful for marker‐assisted selection.